Investigation on neutronic properties of ZrC coated advanced TRISO fuel for high-temperature gas-cooled reactors. (January 2020) - Aziz, F; Panitra, M; Rivai, A K; Silalahi, M; Sabrina, N; Dani, M; Setiawan, M B; Setiadipura, T
Abstract: An experimental 10 MWt power reactor based on high-temperature gas-cooled reactor technology has been planned for Indonesia. The concept was initiated at the end of 2014, and the basic engineering design was completed in 2017. Currently, the development program is focused on detailed engineering design. The type of fuel aimed in the design is a pebble-bed type that contains fuel kernels made of uranium dioxide (UO2) coated in four layers of three isotropic materials. Those layers are a porous buffer layer made of carbon, usually followed by a dense inner layer of pyrolytic carbon (PyC), followed by a ceramic layer of silicon carbide (SiC) to retain fission products, and after that by a dense outer layer of PyC. One of the issues of the fuel system is the problem of corrosion caused by the interaction of fission products such as silver (Ag) and palladium (Pd) with the SiC layer. One of the candidates to resolve the issue is to replace SiC with zirconium carbide (ZrC) which is more resistant to corrosion at high temperatures. In this study, we investigate the effects of the replacement on the neutronic properties of the reactor design at different operating temperatures. For the purpose, we use the SRAC (Standard Reactor Analysis Code) system to calculate the energy spectrum and multiplication factors of the advanced TRISO fuel design. The result of the investigation showed that, in terms of the Doppler coefficient of reactivity, the use of ZrC seems to act more favorably than that of SiC. However, ZrC increases the parasitic neutron capture in the fuel system resulting in lower initial core reactivity which was also confirmed by a slight hardening of the neutron spectrum.